Numerical modelling to assess maintenance strategy management options for a small tidal inlet. (5th March 2017) - Shaeri, Saeed; Tomlinson, Rodger; Etemad-Shahidi, Amir; Strauss, Darrell
Abstract: Small tidal inlets are found to be more sensitive to anthropogenic alteration than their larger counterparts. Such alterations, although typically supported by technical design reports, sometimes require amendments or modification. One of the most suitable tools to conduct the necessary studies in this regard is numerical modelling, since the behaviour of the inlet system in response to proposed remedial actions, can easily be identified. In this paper, various alternative proposals are investigated to determine the most practical and viable option to mitigate the need for ongoing maintenance at a typical small, jettied tidal inlet. The main tool to investigate the alternatives is the hydro-sedimentological modelling of the inlet system, which was performed using the Delft3D software package. The proposed alternative entrance modifications were based upon structural alterations of the inlet system (such as a jetty extension or submerged weir) and non-structural scenarios (such as a change of the time of the dredging campaign or the deposition location of the dredged material). It was concluded that whilst a detailed study is inevitable in order to achieve a comprehensive design plan, based upon the results of this study the construction of a submerged weir at the entrance channel can satisfy the needs of most of the stakeholders, with justifiable costs over a longer period. Highlights: Alternative maintenance strategies for the management of a small, jettied tidal inlet system are investigated. Structural and non-structural options are considered separately. Input reduction and model schematisation techniques are used to conduct the numerical simulation of alternatives. Submerged weir at the entrance channel, extensive back-barrier dredging, and change in time of the annual dredging are worthy options.